TINGKAT KEPUASAN MASYARAKAT TERHADAP FASILITAS PUBLIK PADA RUANG TERBUKA HIJAU KOTA BANDA ACEH - Ziah Afsah Azni Lubis; Iqbal Ahmady; Novita Sari (Journal of Political Sphere, 2022)
AbstractGreen open space is an elongated area/clustered path whose use is open and filled with plants and vegetation that are beneficial to the community, green open space is not only a development in the context of the welfare of the community but also has a positive impact on the environment. The physical development of Banda Aceh City can cause environmental damage such as water, soil and air pollution. Therefore, there is a need for green open space as a balance between the development of Banda Aceh City and the need for clean water and air in Banda Aceh City. An evaluation conducted by the Regional Development Planning Agency regarding the Comfort of Green Open Spaces in Banda Aceh City in 2019 explained that the convenience of the people of Banda Aceh City to the facilities available in green open space is still lacking when viewed from the number of public facilities in Banda Aceh City green open space. Therefore, given the lack of facilities available in green open space, this study aims to determine the level of community satisfaction with public facilities in Banda Aceh city green open space by using green political theory, public service theory and community satisfaction theory. This research is a descriptive quantitative research with data collection methods through questionnaires, observation and documentation. Data processing in this study uses data editing, data transformation and data tabulation methods and is tested using validity tests, reliability tests and Likert scales. The results of this study indicate that the hypothesis (H0) in this study is accepted or in other words the assumption that the level of community satisfaction with public facilities contained in the low open space of Banda Aceh City is indeed true. This is due to the lack of public facilities in Banda Aceh City RTH which affects development services that focus on providing good and comfortable facilities and infrastructure to the community. Based on the results of this study, it is expected that the people of Banda Aceh City can increase their understanding of green open space and it is hoped that the Banda Aceh City Government will provide and repair damaged facilities in green open space. Keywords:Green Space, Public Facilities, and Community Goals.